Isolation and transmission of the Lyme disease spirochete from the southeastern United States. - Oliver, J H (1993)
The isolation of the Lyme disease spirochete (Borrelia burgdorferi) from the southeastern United States is reported. Three isolates, two from cotton mice (Peromyscus gossypinus) and one from the black-legged tick (Ixodes scapularis), were recovered from Sapelo Island, Georgia, in July and September 1991. The spirochetes were characterized by indirect fluorescent antibody assay using a battery of five monoclonal antibodies, by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS/PAGE) of whole cell lysates, and by the polymerase chain reaction (PCR) assay using primers for three DNA target sequences found in B. burgdorferi reference strain B-31. Transmission experiments indicate that the three Georgia isolates can infect experimentally inoculated hamsters and mice. Tick transmission of one of the isolates has been attempted so far; I. scapularis transmitted isolate SI-1 from hamsters to mice, but the lone-star tick, Amblyomma americanum, did not.